Factors influencing adoption of telemedicine technology among health facilities in Yemen - Aljamrh, Bassam Ali Ali (2021)
Telemedicine technology refers to the use of advanced telecommunication technologies for exchanging information related to health or providing healthcare services from distant places. Telemedicine technology has become common worldwide, even in the least developed countries like Yemen, since it helps provide healthcare services over distances, saving time and cost. It helps to provide health care to patients in the remoted areas. In the context of Yemen, the adoption of telemedicine technology in Yemen is limited even though such technological services are needed due to the shortage of healthcare facilities and health physicians. Hence, this study aimed to develop a new model to examine the influence of technological, organizational and environmental factors on the intention to adopt telemedicine technology with awareness and voluntariness as the moderators of these factors. The study employed a quantitative research design, and the data were collected through a survey distributed to 317 managers of healthcare facilities in Yemen through stratified random sampling. The data analysis was done through structural equation modelling SEM, using Smart-PLS since it helps to analyze direct and indirect relationships among research variables. This study integrated Unified Theory of Acceptance and Use of Technology (UTAUT) and Technology-Organization-Environment (TOE) in addition to other factors, including IT infrastructure, perceived security, health facility size, top management support, and trading partner readiness to create the theoretical framework of the study. Besides, awareness and voluntaries were used as the moderators in this framework. Before collecting the primary data, the survey was validated by five experts and then distributed to 30 participants as a pilot test for the survey’s reliability. In the analysis of the pilot test using Cronbach’s Alpha, the factors have values over .70, which shows that the survey has good internal consistency. In terms of the main data, the results showed a significant positive effect for technological factors (IT infrastructure, perceived security, performance expectancy), organizational factors (facilitating condition, health facility size, top management support), and environmental factors (trading partner readiness, and government's support) on intention to adopt telemedicine technology. However, effort expectancy as a technological factor, social influence as an organizational factor, and competitive pressure as an environmental factor were found insignificant in effect on the intention to adopt telemedicine technology. Besides, the most influential factor on intention to adopt telemedicine technology was organizational factors, followed by environmental factors, and technological factors, respectively. From the results of “awareness” and “voluntariness” as moderators, it was found that awareness negatively moderates the effects of the technological and environmental factors on the intention to adopt telemedicine technology; however, it positively moderates the relationship between organizational factors and intention to adopt telemedicine technology. In terms of voluntariness, the findings of the analysis showed that it has a positive moderation on the relationship between technological factors and intention to adopt telemedicine technology; nevertheless, it negatively moderates the relationship between organizational and environmental factors and intention to adopt telemedicine technology. These findings resulted from the investigation through the proposed hypotheses of the theoretical framework showed new relationships and new directions resulted for the moderators’ effects. The outcomes of the research led to implications and recommendations for governments in the least developed countries, the Yemeni Ministry of Public Health (MOPH), policy-makers, and health service providers. This research contributes to the literature in the area of telemedicine adoption by investigating the technological, organizational, and environmental factors influencing telemedicine adoption in the least developed countries through identifying and validating new constructs and integrating the two theories of TOE and UTAUT. In terms of the limitations, the current research is quantitative, and the investigation was limited to the managers of healthcare facilities, while users of telemedicine technologies were excluded. These limitations are provided as directions for future studies to focus on the adoption of telemedicine technologies among users and to use mixed-method design to get an in-depth understanding of the low adoption of telemedicine technologies in the context of Yemen.